2012
DOI: 10.1159/000343099
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Derived Catecholamines Induce a Shift of Th1/Th2 Balance toward Th2 Polarization

Abstract: Aims: Our previous work has shown that lymphocytes synthesize and secrete catecholamines (CAs), which regulate lymphocyte proliferation and apoptosis. In the present study, we explored the effect of the lymphocyte-derived CAs on differentiation and function of T helper (Th) cells. Methods: Lymphocytes were separated from the mesenteric lymph nodes of mice and stimulated by concanavalin A (Con A). These cells were treated with alpha-methyl-p- tyrosine (α-MT), an inhibitor of tyrosine hydroxylase (TH) that is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…These results reveal that TH gene overexpression in lymphocytes promotes a functional bias towards Th2 cells, suggesting that lymphocyte-derived CAs can promote Th cell function towards Th2 polarization. The present data extend our recent findings showing that α-methyl-p-tyrosine (α-MT), an inhibitor of TH, upregulates the expression of T-bet and IFN-γ, but downregulates the expression of GATA-3 and IL-4 in lymphocytes and that pargyline, an inhibitor of monoamine oxydase that degrades CAs, has the opposite effects to those of α-MT (22), supporting the viewpoint that lymphocyte-endogenous CAs regulate the Th1/Th2 balance and promote Th2 polarization. It has been reported that CAs derived from neurons and endocrine cells suppress the cellular immunity and shift the Th1/Th2 cytokine balance towards the Th2 profile (21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results reveal that TH gene overexpression in lymphocytes promotes a functional bias towards Th2 cells, suggesting that lymphocyte-derived CAs can promote Th cell function towards Th2 polarization. The present data extend our recent findings showing that α-methyl-p-tyrosine (α-MT), an inhibitor of TH, upregulates the expression of T-bet and IFN-γ, but downregulates the expression of GATA-3 and IL-4 in lymphocytes and that pargyline, an inhibitor of monoamine oxydase that degrades CAs, has the opposite effects to those of α-MT (22), supporting the viewpoint that lymphocyte-endogenous CAs regulate the Th1/Th2 balance and promote Th2 polarization. It has been reported that CAs derived from neurons and endocrine cells suppress the cellular immunity and shift the Th1/Th2 cytokine balance towards the Th2 profile (21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that exogenous CAs can inhibit the secretion of pro-inflammatory cytokines and promote the release of anti-inflammatory cytokines (21). Although there is recent pharmacological evidence indicating that lymphocytederived CAs induce a shift in the Th1/Th2 balance toward Th2 polarization, that and α 1 -adrenoceptors (ARs) and β 2 -ARs are involved in mediating this effect (22,23), less is known about the role of the AR-coupled signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…they have the enzyme tyrosine hydroxylase for the synthesis of CAs and the enzyme monoamine oxidase for the degradation of CAs [4,37,38,39,40,41]. Our recent study also showed that pargyline, an inhibitor of monoamine oxidase, increased dopamine, epinephrine and norepinephrine in both Con A-stimulated lymphocytes and in the supernatants of the lymphocyte cultures [10,22]. These findings provide a basis for the exploration of the mechanism endogenous CAs exert on lymphocyte differentiation using pargyline.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous CAs can inhibit the secretion of proinflammatory cytokines and promote the release of anti-inflammatory cytokines [21]. We have recently demonstrated that endogenous CAs synthesized and secreted by lymphocytes induce a shift in the Th1/Th2 balance towards Th2 polarization [22]. Although endogenous CAs may exert their effects via an autocrine or/and paracrine pathway, the mechanism underlying endogenous CA-mediated Th differentiation remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al investigated the effect of lymphocyte-derived catecholamines on the differentiation and function of T helper (Th) cells, suggesting that they shifted the Th1/Th2 balance in the direction of greater Th2 polarisation [154155]. Panina-Bordignon et al had earlier suggested that beta2-adrenergic signalling inhibits production of IL-12, thereby promoting Th2 differentiation and inhibiting the Th1 development associated with anti-tumour immunity [156].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%